Aggression and peer rejection among children with conduct disorder - Salehi, Somaieh; Mohd Noah, Sidek; Baba, Maznah; Wan Jaafar, Wan Marzuki (Canadian Center of Science and Education, 2013)
Children with Conduct Disorder suffer from aggression and peer difficulties. This study provides an overview of aggression and peer rejection among children with Conduct Disorder worldwide and in Iran. This study is based on researches from library archives specially focused on studies have been done in Iran. First Conduct Disorder, its’ prevalence, subtypes, and other comorbid disorders are explained. Next, studies regarding aggression among aggressive children and children with conduct problems are reviewed. In this part, the social cognitive deficits of these children are presented based on the model of Social Information Processing. The study followed by researches about peer rejection among children with CD. In addition studies of children with CD in Iran were reconsidered.